HUBUNGAN USIA DAN PEKERJAAN IBU HAMIL DENGAN KEPATUHAN DALAM MELAKUKAN CAKUPAN K4 ANTENATAl CARE DI BPM MARMINA EMPAT LAWANG TAHUN 2020 - Joyce Angela Yunica; Poppy Septiana (Jurnal Kesehatan dan Pembangunan, 2022)
Antenatal care is a haelth service by a professional to a women during their pregnancydone according to the standart of antenatal care service. Pregnant women visit recommended to health service is once in first three semester, once in second three semester, and at least twice in third three semester. This research aimed to find out the relation of pregnant women’s age and jobs with the obedience of doing K4 antenatal care scope at BPM Marmina Empat Lawang in 2020. The population of this reseach was 146 third semester pregnant women doing antenatal care at BPM Marmina. Third semester pregnant women who obeyed were less (22,6%) than those who didnt (77,4%). Third semester pregnancy of low risky aged women were 74,7%, it was less than those who were in high risky pregnance (25,3%). Third semester pregnancy of working women (34,2%), it was less than those who didnt (65,8%). By the result of chi-square test gotten was the relation between pregnant women’s age and the obedience of doing K4 antenatal care scope at BPM Marmina Empat Lawang in 2020 was p-value 0,008. It showed that there was a meaningful relation betweenpregnant women’s age with the obedience of doing K4 antenatal care scope at BPM Marmina Empat Lawang in 2020. By chi-square test that the relation between pregnant women’s job and the obedience of doing K4 antenatal care scope at BPM Marmina Empat Lawang in 2020 was gotten p-value 0,001. It showed thar there was a meaningful relation between pregnant women’s job and tje obedience of doing K4 antenatal care scope at BPM Marmina Empat Lawang in 2020. BPM Marmina Empat Lawang was hoped to be active at ANC service in order pregnant women obey more to examine their pregnancy.